Ứng dụng trò chơi hoá trong giáo dục: Cách thức nâng cao động lực nội tại và hiệu quả học tập trong học tập kết hợp - Doan Ngoc Minh, Huong; Nguyen Viet, Bang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study is conducted to analyse the influences of blended learning on students’ intrinsic motivation and learning outcomes through the mediating role of psychological needs – competence, autonomy, and relatedness based on the self-determination theory. In addition, the research explores the role of gamification as a moderating factor in strengthening these relationships. This study employed a quantitative research approach, using surveys distributed to 362 university students. The study provides empirical evidence on the impact of blended learning on learners’ motivation and performance, as well as the moderating effect of gamification on this relationship. These findings offer practical implications for higher education, particularly in designing effective blended learning models and strategically applying gamification to foster student’s engagement and improve learning outcomes.